Deuterium brain imaging at 7T during D2O dosing. Issue 4 (25th November 2022) - Cocking, Daniel; Damion, Robin A.; Franks, Hester; Jaconelli, Matthew; Wilkinson, Daniel; Brook, Matthew; Auer, Dorothee P.; Bowtell, Richard
Abstract : Purpose: To characterize the ( 2 H) deuterium MR signal measured from human brain at 7T in participants loading with D2 O to ˜1.5% enrichment over a six‐week period. Methods: 2 H spectroscopy and imaging measurements were used to track the time‐course of 2 H enrichment within the brain during the initial eight‐hour loading period in two participants. Multi‐echo gradient echo (MEGE) images were acquired at a range of TR values from four participants during the steady‐state loading period and used for mapping 2 H T1 and T2 * relaxation times. Co‐registration to higher resolution 1 H images allowed T1 and T2 * relaxation times of deuterium in HDO in cerebrospinal fluid (CSF), gray matter (GM), and white matter (WM) to be estimated. Results: 2 H concentrations measured during the eight‐hour loading were consistent with values estimated from cumulative D2 O dose and body mass. Signal changes measured from three different regions of the brain during loading showed similar time‐courses. After summing over echoes, gradient echo brain images acquired in 7.5 minutes with a voxel volume of 0.36 ml showed an SNR of ˜16 in subjects loaded to 1.5%. T1 ‐values for deuterium in HDO were significantly shorter than corresponding values for 1 H in H2 O, while T2 * values were similar. 2 H relaxation times in CSF were significantly longer than in GM or WM. Conclusion: Deuterium MR Measurements at 7T were used to track the increase in concentration of 2 H in brain during heavy water loading. 2 H T1 and T2 * relaxation times from water in GM, WM, and CSF are reported.